COVID-19 Vaccination, Adverse Effect, and SARS-CoV-2 Infection among Couples in Infertility Clinic: A Prospective Study - Seul Gee Park; Eunsun Kwak; Taemi Kim; Young June Choe; Seung-Ah Choe; Jee Hyun Kim (IMR Press, 2023)
Background: Although periconception vaccination is important for maternal and neonatal health, vaccine hesitancy could pose a challenge to achieving a healthy pregnancy in infertile women. We assessed the prevalence of coronavirus disease 2019 (COVID-19) booster vaccination, associated factors, adverse event after vaccination, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among women seeking fertility treatment. Methods: We used the data from participants of the Pregnancy and Urban Environment study (PRUNE study), which is a prospective observational study designed to explore the association between pregnancy and the urban environment in infertile couples. From October 2019 to September 2021, a total of 534 patients provided informed consent and participated in the first and second rounds of a mobile survey conducted at six-month intervals. In the second and third rounds of the survey, we included questions about COVID-19 vaccination and SARS-CoV-2 infection. Adjusted risk ratios (aRR) were calculated for COVID-19 booster vaccination and SARS-CoV-2 infection. Results: All the women participating in the survey had completed the primary series of COVID-19 vaccination. The booster vaccination rate was 38.5%, and the prevalence of SARS-CoV-2 infection was 34.4%. The likelihood of receiving a booster vaccination was higher when women reported alcohol consumption (aRR = 1.90, 95% confidence interval (CI): 1.03-3.51, p = 0.041). SARS-CoV-2 infection was inversely associated with nulliparity (aRR = 0.44, 95% CI: 0.17-1.09, p = 0.077). Among the women vaccinated against COVID-19, 44.3% of respondents reported at least one adverse reaction after receiving the vaccine. Conclusions: All the women participating in the survey had completed primary series of COVID-19 vaccination. The booster vaccination rate was 38.5%, and the prevalence of SARS-CoV-2 infection was 34.4%. Among the vaccinated women, 44.3% reported experiencing at least one adverse reaction after receiving the COVID-19 vaccine. Fever/chilling was the most common (61.8%), followed by abnormal vaginal bleeding/menstrual irregularity (41.8%). A targeted education program by health professionals is needed to promote the benefits of periconception vaccination and reduce the resistance to the COVID-19 vaccine among infertile couples. Clinical Trial Registration: The study was registered at Clinical Research Information Service (https://cris.nih.go.kr/cris/info/dataset.do), registration number: KCT0003560.